Effect of acute alcohol consumption on blunt bowel mesenteric injury: a retrospective analysis - Ting-Min Hsieh; Kuo-Chen Huang; Po-Chun Chuang; Chun-Ting Liu; Bei-Yu Wu; Ching-Hua Hsieh; Fu-Jen Cheng (BMC Emergency Medicine, 2024)
Abstract Background The effect of alcohol consumption on trauma remains controversial. The effects of alcohol on hemorrhage and peritonitis after blunt abdominal trauma have rarely been discussed. This study aimed to explore the effects of acute alcohol intoxication on the clinical characteristics, injury patterns, and outcomes in a surgical blunt bowel mesenteric injury (BBMI) cohort. Methods A retrospective data analysis was performed using trauma cases of patients who had been tested for alcohol and had surgically proven BBMI from a Trauma Registry System from 2009 to 2021. Patients were grouped according to their positive blood alcohol concentration (BAC; >0.5% vs. no BAC; less than 0.5% no BAC) upon arrival at the emergency department (ED). The injury characteristics, physiological parameters, and outcomes with respect to post-injury complications and mortality were assessed. Results In total, 142 patients with surgical BBMI were included. Of these, 116 and 26 patients were assigned to the BAC-negative and BAC-positive groups, respectively. The overall injury severity, injury pattern, and age were comparable between the groups. The patients in the BAC-positive group had a significantly lower systolic blood pressure (99 mmHg vs. 119 mmHg; p = 0.046), worse shock index (0.96 vs. 0.82; p = 0.048), and lower percentage and number of packed red blood cells transfused (34.6% vs. 57.8%; p = 0.032 and 0 U vs. 2 U; p = 0.031) than those in the BAC-negative group. Additionally, although not statistically significant, patients in the BAC-positive group had lower leukocyte counts (9,700 cells/mm3 vs. 11,600 cells/mm3; p = 0.165 ) at the ED. However, significantly reduced percentages of leukocytes ≥ 12,000 cells/mm3 (26.9% vs. 48.3%; p = 0.048) and ≥ 12,000 or ≤ 4,000 cells/mm3 (26.9% vs. 50.9%; p = 0.027) were observed in the BAC-positive group at the ED. Furthermore, the 30-day mortality rate did not show statistically significant differences, and there was a higher incidence of bowel-related mortality in the BAC-positive group (11.5% vs. 1.7%, p = 0.043). Conclusions For patients with BBMI arriving alive to the hospital, acute alcohol consumption was associated with significantly worse hemodynamic parameters, interfered inflammation status, and higher bowel related mortality rate.